The effects of deforestation on rural women: case of Chiwundura - Mbulayi, Rumbidzayi Brenda (Midlands State University, 2014)
The research focused on the effects of deforestation on rural women, a case study being Chiwundura. Chiwundura is a former tribal trust land found within the Midlands province characterised by limited vegetation cover as a result of alarming deforestation rates common in the area. The research problem was that deforestation leads to various implications such as climate change, soil infertility, siltation, extinction of flora and fauna, poverty and drought resulting from the loss of nutrients and organic matter retained in the forest ecosystems. Due to these implications rural women have somehow been affected socio-economically physically and even psychologically. Women need to travel long distances in search of firewood, tiling unproductive infertile lands to grow their crops, have their health threatened by these implications and or, spend more time on domestic chores rather than economic or community development activities that can improve their livelihoods. To find the root cause of these effects the research looked at environmental policies, pre-colonial and current to appreciate the emanation of deforestation. Literature review helped define the term deforestation, outline the causes and effects brought by deforestation as suggested by various scholars. The literature review elaborated how women are affected as a result of deforestation. The research methodology focused on data collection tools, target population, sampling techniques and the procedures for data collection. Questionnaires and interviews were the main tools used to collect data from the respondents who involved the Chiwundura community, Forestry Commission, E.M.A, A.R.E.X and Vungu RDC employees. The target population was 91 respondents. The researcher used both non-probability and probability sampling techniques which involved purposive sampling and simple random sampling respectively to access the targeted population. The fourth chapter links the findings to the research objective and literature review so as to match what has been said by other scholars and what is on the ground. In total 80 questionnaires were distributed among 4 wards, 9, 10, 11, and 12, and the response rate was 86%. 10 interviews were conducted among the Vungu RDC, E.M.A, Forestry Commission and A.R.E.X officials and the response rate was 91%. Data was presented in tables and pie charts with a brief interpretation and description of the data. Respondent’s assumptions on the cause and the various implications of deforestation to women were well laid down. Respondents provided information on the possible solutions they assumed would solve their problems. The major findings of this research showed that there is excessive deforestation in the Chiwundura and women are being affected by it although some respondents argued that both men and women were equally affected by it. The last chapter gave a summary of the research, conclusions drawn and possible recommendations on addressing the effects of deforestation on rural women.